Batbuyan Batjav's research comments on Mongolia, September 2021 (Mobilities and Socialities: COVID-19 in the Drylands of Africa and Beyond, 2021)
Includes photographs
Keywords: Arid regions; Herders; Disasters; Subsidies; Weather; Livestock; Agriculture; Education; Schools; Local government; Household Income; Lockdown; Dzud (Mongolia); Mongolia; COVID-19 Pandemic